Clinico mycological profile of Dermatophytosis in patients attending tertiary care hospital in Northern India - Aishiya Ishrat,; Saba Choudhary,; Masarat Jabeen, (Asian Journal of Medical Sciences, 2022)
Background: Dermatophytoses refers to superficial fungal infection of keratinized tissue caused by keratinophilic dermatophytes. It is most common superficial cutaneous infection of stratum corneum affecting hair, nail, and skin. Aims and Objective: The aim of this study was to study the clinico-mycological profile of dermatophytic infection that are prevalent in this region. Materials and Methods: Samples were collected from 104 patients which included skin, nail, and hair samples after the detail history and examination of patients. The samples were subjected to direct microscopy and culture. Further identification was done by microscopic and macroscopic characteristics of fungal pathogens. Results: A total of 104 cases were positive for dermatophytic infection. Among the dermatophytic infections, Tinea corporis (63.4%) was most common clinical type followed by Tinea cruris (18.3%). Males (66.3%) were affected more than females (33.6%) and the age group most affected was 31-45 yrs (46.2%) followed by 16-30 yrs (32.7%) in the current study. Of all the dermatophyte isolates T.rubrum was the most common (77.4%) cause of infection, followed by T. mentagrophytes (12.7%). Conclusion: The present study reveals the varying trend in the incidence of dermatophyte species which is important to implement treatment regimens and to recommend control measures.